Big Small Steps: Childhoods on the Move - Sanfilippo-Schulz, Jessica (Satura, 2018)
In May, shortly before boarding the Milano Malpensa airport Express train at the station of Cadorna, a stone set into the floor caught my eye. Passengers of the Malpensa Express who have the time to take a closer look at the stone can read an engraved inscription in Italian and English: “Every step I have taken in my life has led me here, now” (Garutti). After a 50-minute train ride, the inscription can be found inside the Milano Malpensa airport too, emphasizing both the significance of transport and the places of transit for travellers. These works of public art by the Italian artist Albert Garutti inspire travellers to think about the deeper meaning and consequences of each of their infinite steps, journeys, actions and decisions. Why we are physically in this certain place, right now, is often connected to moves we deliberately chose to make in adulthood, for example, family or job related. Yet, for many individuals, moves which can determine the course of one’s life are made in childhood due to their parents’ choices. Thus some of the “steps” which have led them to certain locations were not taken of one’s own free will but involuntarily. For work reasons, at the end of the 1960s, my British mother and Italian father moved to Liberia in West Africa, where I would eventually see the light of day. After eight years, due to the deteriorating political situation, my parents decided to move to Italy, where my siblings and I attended a British school. For love, years later, I moved to Germany. Due to my family’s background, relocating was not an unknown experience and my first German steps were taken in Stuttgart. Subsequently in 2004, two weeks before delivering our baby, my husband and I moved to Münster, where I began my Bachelor studies in 2008. By virtue of my cross-cultural upbringing, I then decided to enrol in the Master of Arts programme “National and Transnational Studies”. During the very first weeks of this programme, whilst discussing the term natio, we were asked by a lecturer to explain what home meant to us. Many peers replied that home was where they were born or where they grew up. Somewhat perplexed, that same evening I immediately searched the whole Internet for the definition of home when one has multiple passports (in my case three), attachments and languages. Seconds later, Google informed me that having grown up “among worlds”, I am a Third Culture Kid.